Codes in the Atomic Weights of Chemical Elements - Kurić, Lutvo (International letters of chemistry, physics and astronomy, 2014)
The subject of this thesis is a digital approach to the investigation of the digital basis of digital Periodic Table. The digital mechanism of this Table have been analyzed by the application of cybernetic methods, information theory and system theory, respectively. This paper is to report that we discovered new methods for development of the new technologies in chemistry. It is about the most advanced digital technology which is based on program, cybernetics and informational systems and laws. The results in practical application of the new technology could be useful in chemistry, bioinformatics, genetics, bio-chemistry and other natural sciences